The night before Christmas - Moore, Clement Clarke, 1779-1863 (Harper, an imprint of HarperCollinsPublishers, 2020)
In Loren Long's touching interpretation of "Twas the night before Christmas," readers are invited to visit the homes of four families-- each on Christmas Eve. What do these four homes share? The excitement and anticipation of the most splendid night of the year. In this reimagined tale, the author and illustrator reminds us that no matter where we live, all children share the same wish for Christmas magic.